2010
DOI: 10.3989/scimar.2010.74n4717
|View full text |Cite
|
Sign up to set email alerts
|

First record of the Indo-Pacific fish the Jarbua terapon (<i>Terapon jarbua</i>) (Osteichthyes: Terapontidae) in the Mediterranean with remarks on the wide geographical distribution of this species

Abstract: SUMMARY: The Indo-Pacific fish Terapon jarbua is recorded for the first time in the Mediterranean. This record is evidentially the result of T. jarbua entering the Mediterranean via the Suez Canal (Lessepsian migration). The present record increases the total number of known Lessepsian fish to 74. A comparison of Mediterranean and Red Sea specimens of T. jarbua with specimens from the Far East suggests the necessity for genetic studies in order to clarify the unity of this taxon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 11 publications
(7 reference statements)
1
8
0
Order By: Relevance
“…They show frequency characteristics and daily pattern similar to Therapon theraps as recorded in the Great Barrier Reef in Australia and Arabian Sea (Mahanty et al 2015, McCauley & Cato 2000. Therapon theraps is typical from Indo-West Pacific and Australian waters, but individuals of this species and of Therapon jarbua, have been reported in the Mediterranean Sea along the Aegean (Minos et al 2012), Adriatic (Lipej et al 2008) and Israeli coasts (Golani & Appelbaum-Golani 2010). They are considered invasive species, probably arrived in Mediterranean through a Lessepsian migration.…”
Section: Discussionmentioning
confidence: 57%
“…They show frequency characteristics and daily pattern similar to Therapon theraps as recorded in the Great Barrier Reef in Australia and Arabian Sea (Mahanty et al 2015, McCauley & Cato 2000. Therapon theraps is typical from Indo-West Pacific and Australian waters, but individuals of this species and of Therapon jarbua, have been reported in the Mediterranean Sea along the Aegean (Minos et al 2012), Adriatic (Lipej et al 2008) and Israeli coasts (Golani & Appelbaum-Golani 2010). They are considered invasive species, probably arrived in Mediterranean through a Lessepsian migration.…”
Section: Discussionmentioning
confidence: 57%
“…Finally, whereas 'traditional' diversity indices loose species identity making difficult to distinguish whether changes in biodiversity are related to specific species or to community composition (Lamb et al, 2009;Zhao et al, 2014), the N 90 value is provided with a list of contributing species. This allows a traceability of species turnover and may be relevant to monitor the spreading of non-indigenous species (Galil, 2007;Lamb et al, 2009), a global phenomenon that is especially important in the Mediterranean (Galil, 2007;Golani and Appelbaum-Golani, 2010). The application of the N 90 diversity index to the case study showed that it may be an alternative to 'traditional' diversity indices when trying to monitor fishing impacts and the effects of environmental changes.…”
Section: Discussionmentioning
confidence: 96%
“…Terapon jarbua is classified as least concern (LC) under the IUCN Red List due to its widespread distribution with no known threats (Dahanukar et al 2017). The native distributional ranges of the crescent grunters include Australia, Bangladesh, Cambodia, China, India, Indonesia, Japan, Malaysia (Du et al 2019;Shyama et al 2020), Mediterranean (Golani and Appelbaum-Golani 2010), Myanmar, Philippines, Red Sea, Sri Lanka and Taiwan (Froese and Pauly 2018).…”
Section: Introductionmentioning
confidence: 99%